IMPLEMENTASI LIGHT FOOTPRINT STRATEGY AMERIKA SERIKAT DALAM MENANGANI KELOMPOK AL SHABAAB DI SOMALIA - Kalwa El Chirri; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
United States took an important role in eradicating terrorism after 9/11, and the War on Terrorism was born. Somalia is a country that has had a prolonged conflict since President Siad Barre experienced the emergence of groups that were initially rebellious against the government. Then these groups became militant groups and even affiliated with global terrorism. One of the largest groups is Al Shabaab. This study aims to find out how to implement the Light Footprint Strategy. This strategy is a military strategy since President Barack Obama is known to eradicate attacks.To research this topic, the research method used is qualitative, to explain the implementations carried out by the United States in eradicating Al Shabaab. Then the theory used is the implementation of policies by Merilee S. Grindle, which explains how a policy becomes possible to be realized. The perspective used is realism. Given the above background, the author decided to use the concept of national interest, where the United States has a specific goal in implementing the strategy, and collected data using Library Research methodThe results of this thesis show that the implementation of policy carried out by the US can kill several key Al Shabaab leaders, so far the acceptable result is the death of Al Shabaab leaders, then the US claims the success of its air strikes. Unfortunately, Al Shabaab's presence in Somalia is quite strong in Africa.Key Words : Al Shabaab, War on Terrorism, Policy Implementation, National Interest.